Wedge pore modelling of gas adsorption in activated carbon: Consistent pore size distributions. (30th September 2020) - Loi, Quang K.; Prasetyo, Luisa; Tan, Johnathan (Shiliang); Do, D.D.; Nicholson, D.
Abstract: The pore size distribution ( PSD ) of a porous solid is usually obtained by matching the experimental adsorption isotherm for argon or for nitrogen at their boiling points against a theoretical isotherm constructed with models of non-connected pores. The seminal work of Rosalind Franklin in 1951, showed that the pore spaces have wedge geometry rather than the parallel side slits commonly used in carbon pore modelling. Based on this, we proposed a wedge geometry for pores as a basis for modelling adsorption in activated carbon; thereby introducing a paradigm shift from the customary slit geometry. Not only does the wedge geometry better reflect the physical pore space, it accounts for the linear connectivity which is absent in the current PSD modelling. We have used extensive simulations to obtain a theoretical isotherm and use it to match experimental isotherms for argon and nitrogen to check the invariance of the PSD with respect to the adsorbate molecule. In this new model, the artefact of zero pore volume at 1 nm, which can occur in the slit model, is absent. Apart from the self-consistency of the derived PSD, the new wedge model also gives a good account for the isosteric heat versus loading. Graphical abstract: Image 1 Highlights: A paradigm shift in the modelling of activated carbons using wedge pores. Smooth pore size distribution ( PSD ) for activated carbons. Agreement between PSD s obtained with argon or nitrogen at their boiling points. Simulated isosteric heats which are in good agreement with experiment.